2022
DOI: 10.1080/03014460.2022.2129091
|View full text |Cite
|
Sign up to set email alerts
|

Bio-banding in soccer: past, present, and future

Abstract: Maturity-related selection biases are engrained within professional academy soccer programmes. The process of grouping of children by biological maturity ("bio-banding"), rather than age is not new. However, practice of bio-banding is becoming increasingly popular with youth soccer development programmes where maturity-related differences in size and athleticism have been cited as key mechanisms behind the over-selection of early over late maturing players. However, the objectives of bio-banding require furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…provided a challenging game environment that gave less mature players the opportunity to demonstrate key skills and psychological characteristics considered desirable during the IT process, which could possibly be hidden during a CA competition. While this may be true, it needs to be addressed in better detail, and special attention should be paid to the impact of BB on talent assessments (Towlson & Cumming, 2022).…”
Section: Technical-tactical and Physical Aspectsmentioning
confidence: 99%
“…provided a challenging game environment that gave less mature players the opportunity to demonstrate key skills and psychological characteristics considered desirable during the IT process, which could possibly be hidden during a CA competition. While this may be true, it needs to be addressed in better detail, and special attention should be paid to the impact of BB on talent assessments (Towlson & Cumming, 2022).…”
Section: Technical-tactical and Physical Aspectsmentioning
confidence: 99%
“…These psychological aspects are important for talent identification, as late-maturing players have been characterised as being achievement-oriented and highly skilled (between 13 and 14 years; [16]), which might be linked, in part, to the onset and cessation of peak height velocity (PHV) [17,18]. For instance, our previous findings have shown that performing in maturity mis-matched (i.e., late maturing versus early maturing) categorised groups of players (using 'bio-banding'; [19][20][21]) during small-sided games provides late-maturing players with a mis-matched environment which allows them to exhibit a number of desirable psychological characteristics [22]. This maturity-related performance phenomena can be in part explained by the 'underdog hypothesis' [15,23], which proposes that late-maturing players may have established enhanced psychological skills that permit them to compete with their more mature team mates on equal terms [23].…”
Section: Introductionmentioning
confidence: 99%